Enzyme-triggered self-assembly of gold nanoparticles for enhanced retention effects and photothermal therapy of prostate cancer. Issue 70 (15th August 2018) - Yang, Shuyan; Yao, Defan; Wang, Yanshu; Yang, Weitao; Zhang, Bingbo; Wang, Dengbin
Abstract : A peptide-modified gold nanoparticle was developed for tumour-targeted therapy. Abstract : A peptide-modified gold nanoparticle was developed for tumour-targeted therapy. Triggered by alkaline phosphatase, the CREKA-YP FFK(Nph) peptide can self-assemble and further result in accumulation of gold nanoparticles in tumour cells. The large-sized gold nanoparticle aggregates cannot escape from the tumour tissue, therefore realizing the goal of tumour-specific targeting, enhanced retention and photothermal effects.